VISIBLE SPECTROPHOTOMETRIC METHOD FOR ESTIMATION OF BISOPROLOL FROM ITS BULK AND TABLET FORMULATION - T. KUMBHAR, SMITA; P. SHINDE, PANKAJ; B. SHINDE, DATTATRYA; B. SOLANKAR, PAYAL (Asian Journal of Pharmaceutical and Clinical Research, 2013)
The proposed method is new, simple, sensitive, reproducible, economical, accurate and precise and can be successfully applied in estimation of bisoprolol. This method can find applications in clinical studies and therapeutic drug monitoring. This method of colorimetric estimation of bisoprolol is based on the formation of blue colored chromogen when reacted with ferric chloride and pottasium ferricynide. The concentration of bisoprolol over range ofÂ 1- 13 micro g/ml was found to obey Beer's law in the stated range. The blue colored complex has absorption maxmia at 770 nm with molar absorptivity and sandell's 2.2387 x 104 lit mol-1 cm-1 and0.0154 micro g/cm2/0.001 absorbance units, reproducible, specific, and the reagent was not found to react with the soluble matters of the body fluids. The results analysis were validated as per ICH Q2B guidelines. Keywords: Bisoprolol, visible spectroscopy, validation